Characterization of municipal waste waters - Mbewe, Alfred; Mbewe, Alfred (Urban Water Management, 2017)
Over the past 20 years there have been extensive developments in the activated sludge method of treating wastewater. The functions of the single sludge system have expanded from carbonaceous energy removal to include progressively nitrification, denitrification and phosphorus removal, all mediated biologically. Not only has the system configuration and its operation increased in complexity, but concomitantly the number of biological processes influencing the system performance and the number of compounds involved in these processes have increased. With such complexity, designs based on experience or semi-empirical methods no longer will give optimal performance; design procedures based on more fundamental behavioural patterns are required. Also, it is no longer possible to make a reliable quantitative, or sometimes even qualitative prediction as to the effluent quality to be expected from a design, or to assess the effect of a system or operational modification, without some model that simulates the system behaviour accurately. To address these problems, over a number of years design procedures and kinetic models of increasing complexity have been developed, to progressively include aerobic COD removal and nitrification (Marais and Ekama, 1976; Dold et al., 1980), anoxic denitrification ( van Haandel et al., 1981; WRC, 1984; Henze et al., 1987; Dold et al., 1991) and anaerobic, anoxic, aerobic biological excess phosphorus removal (Wentzel et al., 1990; Wentzel et al., 1992; Henze et al., 1995). In terms of the framework of these design procedures and kinetic models, the influent carbonaceous (C) material (measured in terms of the COD parameter) is subdivided into a number of fractions - this subdivision is specific to the structure of this group of models. The influent COD is subdivided into three main fractions, biodegradable, unbiodegradable and heterotrophic active biomass. The unbiodegradable COD is subdivided into particulate and soluble fractions based on whether the material will settle out in the settling tank (unbiodegradable particulate) or not (unbiodegradable soluble). The biodegradable material also has two subdivisions, slowly biodegradable (SB COD) and readily biodegradable (RBCOD); this subdivision is based wholly on the dynamic response observed in aerobic (Dold et al., 1980) and anoxic/aerobic (van Haandel et al., 1981) activated sludge systems, that is, the division is biokinetically based. Thus, as input to the design procedures and kinetic models, it is necessary to quantify five influent COD fractions, that is, to characterize the wastewater COD. From a review of the literature on existing tests to quantify the COD fractions, it was evident that the existing procedures are either too elaborate or approximate or sometimes not even available. This research project addresses these deficiencies. In this research project, the principal objective was to develop simple accurate procedures to quantify the influent wastewater COD fractions. A batch test method has been developed to quantify the five influent COD fractions; namely heterotrophic active biomass, readily biodegradable COD, slowly biodegradable COD, unbiodegradable particulate COD and unbiodegradable soluble COD. Also, the physical flocculation-filtration method of Mamais et al. (1993) to quantify RBCOD has been evaluated and refined.